2009
DOI: 10.1021/jp811082p
|View full text |Cite
|
Sign up to set email alerts
|

Configuration-Driven Unitary Group Approach for Generalized Van Vleck Variant Multireference Perturbation Theory

Abstract: A new, efficient, configuration-driven algorithm utilizing the unitary group approach (UGA) was developed and implemented for the generalized van Vleck perturbation theory (GVVPT) variant of multireference perturbation theory. The computational speed has been improved by 1 or 2 orders of magnitude compared to the previous implementation based on the Table-CI technique. It is shown that the reformulation is applicable to both the second-order (GVVPT2) and third-order (GVVPT3) approximations. Calculations on mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 24 publications
0
51
0
Order By: Relevance
“…It was demonstrated that, despite the complexity of the GVVPT2 resolvent (e.g., the presence of the highly nonlinear hyperbolic tangent function) and the relaxation of the primary subspace, computationally amenable algorithms could be realized. Because the algorithm can use all of the advantages of the GVVPT2 energy calculations (e.g., macroconfiguration-and configuration-based screening and graphical unitary group approach (GUGA) evaluation of matrix elements [17]), efficient computer codes can be developed. In particular, the prototype computer code that realized the Lagrangian-based GVVPT2 dipole formalism described in this Letter was observed to require no more than 2.5 times the amount of computer time than does the GVVPT2 energy code; additional optimizations can be expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that, despite the complexity of the GVVPT2 resolvent (e.g., the presence of the highly nonlinear hyperbolic tangent function) and the relaxation of the primary subspace, computationally amenable algorithms could be realized. Because the algorithm can use all of the advantages of the GVVPT2 energy calculations (e.g., macroconfiguration-and configuration-based screening and graphical unitary group approach (GUGA) evaluation of matrix elements [17]), efficient computer codes can be developed. In particular, the prototype computer code that realized the Lagrangian-based GVVPT2 dipole formalism described in this Letter was observed to require no more than 2.5 times the amount of computer time than does the GVVPT2 energy code; additional optimizations can be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Since the GVVPT2 method [3] and its high performance implementation [17] have been described in previous publications, here only salient features critical to the evaluation of the electric dipole are reviewed. In GVVPT2, the configuration space, in which the N Plowest electronic states are sought, is divided into two subspaces: a model MCSCF subspace, L M (dim L M > N P ), specified by a given set of reference electron configurations, and an external subspace, L Q , whose configurations are related to the reference ones through single and double excitations (N.B.…”
Section: Synopsis Of Gvvpt2mentioning
confidence: 99%
“…In order to avoid higher-order reduced density matrices ( and also to simplify the analytical energy gradients), the partially contracted scheme has also been proposed by Werner and coworkers for CASPT2 31,68,69 . Another interesting development is the generalized van Vleck PT (GVVPT) of Hoffmann and coworkers 70,71 . They showed the way to tackle large active spaces via the use of macroconfigurations and also discusses very nicely how to avoid the intruder problem.…”
Section: Introductionmentioning
confidence: 99%
“…3. The R e , x e , x e x e , B e , D e and D 0 values we obtain for the X 1 R þ HF are of 0.9175 Å , 4133.79, 88, 20.77, 0.00210 cm -1 , and 158.88 (kcal/mol) at the CBS 16 15 In this article, authors study the difference between the various direct perturbation theory and Pauli perturbation method for the HX (X = F,Cl, Br, and I) molecules in order to investigate the relative importance of relativistic effects, higher-order electron correlation effects, and remaining basis sets effects. 16 To obtain the results at CBS limit, we have used the same scheme as done by Hirata et al [68].…”
Section: The Ss-mrmppt Results With Different Basis Setsmentioning
confidence: 58%
“…From the previously published data due to Klopper et al [92] 15 (computed at CCSD(T) level including a first-order relativistic correction obtained from an analytical evaluation of the first-order direct perturbation energy at the CCSD level in conjunction with large one-particle basis sets), it is found that the overall accuracy of the spectroscopic constants for the HF system is clearly dominated by electron correlation and basis set truncation effects, while the relativistic effects are of minor importance. Although we observe that the shapes of PESs generated via CASS-CF(2,2) and SS-MRMPPT/CAS(2,2) methods are very similar, as shown in the table, the dynamical correlation effects on the spectroscopic properties of HF are noticeable.…”
Section: Numerical Applications and Discussionmentioning
confidence: 99%